Faktor – Faktor Yang Memengaruhi Earnings Response Coefficient - Giofanny, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to analyze the influence of Firm Size, Profitability, Leverage, and Company's Growth on Earnings Response Coefficient (ERC). This study uses 180 data samples of manufacturing company listed on the Indonesia Stock Exchange from 2017-2019. The sampling techniques used by using purposive sampling. This study uses Eviews 11.0 for windows software to process data. The results of this study show that Profitability has a positive and significant effect on the Earnings Response Coefficient (ERC) while Firm Size, Leverage, and Company's Growth have no significant effect on the Earnings Response Coefficient (ERC). The implication of this study is the need to increase management focus in generating profits which will increase the value of the Earnings Response Coefficient (ERC) which will bring a good signal for investors.